The Implementation of Think Pair Share (TPS) Learning Model using Realistic Mathematics Approach in Problems Solving - Ita Milandari Khotimah; Marhan Taufik; Hendarto Cahyono (MEJ (Mathematics Education Journal), 2019)
This research aimed at describing the implementation of TPS learning model using Realistic Mathematics Approach in solving problems. The type of research was qualitative descriptive. The subjects of this research were the students of class 8-I that consisted of 20 students. The data collection methods that used in this research were: 1) observation, 2) test, 3) interview, and 4) documentation. The research results indicated that the learning used the TPS model using the Realistic Mathematics Approach in the geometry material of prism and pyramid during four-time meetings overall could be conducted based on what had been planned. The learning stages are adjusted to the students’ learning activities in order to improve the students’ thinking abilities and skills to solve the problems. The students’ mathematical problem-solving ability was high categorized after the implementation of this learning model. It was proven by the test results which indicated that the students were able to master the three important stage namely understanding the problems, planning the completion, and implementing the plans. The understanding stage was by writing down the information from the problems and the information that had been asked from the question very well. In the planning stage, the students also could write down the information into the mathematical model and plan the completion strategy even though it was not complete enough. Therefore, in the model of implementing the plan, the students were able to implement the completion based on the plans and get the results.